Preparation of Green-Emissive Zinc Oxide Composites Using Natural Betacyanin Pigment Isolated from Red Dragon Fruit - Yehezkiel Steven Kurniawan; Hendrik Oktendy Lintang; Leny Yuliati (Indonesian Journal of Chemistry, 2021)
In this work, we reported the synthesis of green-emissive composite materials of zinc oxide (ZnO) and isolated betacyanin pigment from red dragon fruit (RDF) extract utilizing organic linkers, i.e. (3-chloropropyl)trimethoxysilane (CPTMS) and (3-aminopropyl)trimethoxysilane (APTMS). Betacyanin was extracted using a maceration technique, while CPTMS-ZnO and APTMS-ZnO were prepared by mixing ZnO and the respective organic linker in ethanol. The obtained ZnO/CPTMS and APTMS-ZnO composites were separately added into the RDF extract, followed by stirring at room temperature for 24 h. As high as 80 and 90% of betacyanin was successfully impregnated onto CPTMS-ZnO and APTMS-ZnO, respectively. A comparison study was made by preparing RDF-CPTMS and RDF-APTMS first and then introducing them onto ZnO. In this case, as high as 81 and 100% of betacyanin in RDF-CPTMS and RDF-APTMS, respectively, were impregnated onto ZnO. These results revealed that APTMS was a better organic linker than CPTMS and the order of the steps to introduce APTMS was important. The presence of betacyanin on the composite materials was confirmed by FTIR and fluorescence spectroscopy. All the composite materials had an excitation signal at 426–428 nm and emission signals at 459 and 517–518 nm, demonstrating their promising application as green-emissive materials.